Development of a noble aluminum‐pigmented metallic polymer: Recommendations for visible flow and weld line mitigation. Issue 37 (11th February 2020) - Lim, Jung Seop; Ban, Soo Hyung; Kim, Dong Sup; Kwon, Kwang Yeol; Lee, Sang Hoon; Lim, Jong Kwan; Cho, Sung Hwan
Abstract: We investigated the appearance of flow and weld lines when metallic pigments are used in polymer blends and how such lines can be eliminated by improving the pigment particle shape and optimizing pigment loading. Acrylonitrile butadiene styrene copolymer and two types of aluminum flakes, lamellar and three‐dimensional (3D), were blended in a twin‐screw extruder with a screw diameter of 25 mm. The temperatures from the hopper to the nozzle were 140, 180, 220, 220, 220, 220, and 220°C. Weld and flow lines were observed using field‐emission scanning electron microscopy and energy dispersive X‐ray spectroscopy of specially manufactured injection specimens. In the flow line region, traditional lamellar flakes were randomly oriented, while 3D flakes exhibited a distinct and stable orientation. Based on these observations, flow and weld lines in a finished metal/polymer blend can be minimized by using 3D metal particles in place of lamellar flakes. We also investigated the effects of aluminum flake loading on weld and flow line visibility. At low loading, weld lines were clearly visible due to the lack of pigmentation in the front of the polymer flow. Conversely, high loading resulted in relatively high concentrations of pigment near the weld line area, reducing weld line visibility. These findings suggest that there is an optimum metal loading level where the visibility of flow and weld lines is minimized. Abstract : Energy dispersive X‐ray spectrometry images of samples containing 2 wt% of two types of flakes. (a) Lamellar flakes, normal region; (b) Lamellar flakes, flow line region; (c) 3D flakes, normal region; and (d) 3D flakes, flow line region.